PELATIHAN EMOTIONAL INTELLIGENT UNTUK MENINGKATKAN SERVICE QUALITY PADA FRONTLINER DI SALAH SATU PERGURUAN TINGGI SWASTA - Widodo, Mochamad Sigit; Hariyanto, Heru (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Service Quality is an important asset for higher education institutions, because this Service Quality can have the most important impact on service recipient satisfaction, and finally if service satisfaction occurs repeatedly, customer loyalty or customer satisfaction is formed (Tjiptono, 2008). The implementation of Service Quality by the right service provider (fronliner) will be able to provide satisfaction. Therefore, there is a need for Emotional Intelligent training to improve Service Quality at the frontliner of one of the private universities in Surabaya. Participants in the "Excellence Service are Excellence People" training totaled 28 frontline staff employees. Based on research conducted Emotional Intelligent training to improve Service Quality has a significant influence with results that show that from the results of paired T testing, significance values are obtained which show that there is a difference between emotional intelligence before and after training or it can be concluded that there is a significant influence between emotional intelligence before training and after training. In addition, the results of paired T tests on Service Quality also showed a significance value of 0.000 where the significant value was less than alpha 0.05. Which means that there is a difference between the quality of service before and after training or it can be concluded that there is a significant influence between the quality of service before training and after training. So that the conclusion is that emotional intelligence training significantly has an increasing impact on EI and an increase in service quality.